PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PENGUASAAN KONSEP BIOLOGI SISWA - Lena Rista Saragih; Ramadhani Fitri; Helendra . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
The ability to master the concept is a very important ability to be improved. Discovery learning learning model is a learning model that has 6 stages of learning that are able to support the achievement of mastery of concepts. This study aimsto determine the effect of the discovery learning model on students’ mastery of biological concepts through literature study, namely by looking for various sources that are relevant and have ISSN which are used as references and guidelines. This research method is a literature study by looking for relevant reference sources. The population and sample in this study were all relevant literature articles. Results Based on the literature study research, discovery learning model has an effect on students’ mastery of biological concepts. This means that students’ mastery of biological concepts is significant to the discovery learning model. The discovery learning model can be used as a learning model in schools, especially in biology subjects.